Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil - de Santana, Carlos D.; Crampton, William G.r. (Zootaxa, 2006)
Sternarchorhynchus curumim, a new species of tube-snouted ghost knifefish, is described from the main river channel of the Rio Tefé, in the lowland Amazon basin of Brazil. This species is diagnosed from congeners on the basis of body and fin pigmentation, meristic characters such as number of scales above the lateral line at mid-body, and morphometric characters such as relative body proportions. We also provide notes on the ecology and electric organ discharges of this species.Resumo. Sternarchorhynchus curumim, uma espécie nova de ituí, é descrita do canal principal do rio Tefé na bacia Amazônica do Brasil. Esta espécie é diagnosticada dos congêneres com base na pigmentação do corpo e das nadadeiras, caracteres merísticos tal como, o número de escamas acima da linha lateral no centro do corpo, e caracteres morfométricos como as proporções corporais. Nós também, fornecemos notas sobre as descargas do órgão elétrico e ecologia desta espécie.